Dynamics simulation approach in model development of unsold new residential housing in Johor / Lok Lee Wen and Hasimah Sapiri - Lok, Lee Wen; Sapiri, Hasimah (2021)
The unsold units of residential housing in Malaysia were surged significantly in four consecutive years starting from 2015 and Johor was ranked as the highest in unsold housing over other states in Malaysia. Therefore, this study aims to identify the causal factors of unsold new residential housing and to analyse the dynamic relationship between the causal factors, unsold new housing, and the housing market in Johor. First, the model was developed to present the dynamic relationship between the factors and the unsold housing using a system dynamics approach, then the simulation results were compared with the real data, called the behavioural validity test. After that, the model was validated through the least square method. Results showed three main factors that influenced unsold new housing stocks in Johor: house prices, housing demand and housing supply. Meanwhile, those three main factors were affected by other aspects, such as household income, demand for housing loans, inflation rate and construction cost.